Mesenchymal stromal/stem cell-derived exosomes as a potential therapeutic approach to osteoarthritis combined with type 2 diabetes mellitus - Xie, Siyi; Liu, Meiling; Kong, Yajie; Yang, Yiming; Chen, Ruixue; Wang, Yuzhong; Cao, Shuxing; Song, Yongzhou (Frontiers in Cell and Developmental Biology, 2025)
Osteoarthritis (OA) and type 2 diabetes mellitus (T2DM) often coexist due to shared risk factors and high prevalence, but effective treatment methods are currently lacking. Mesenchymal stromal/stem cell-derived exosomes (MSC-Exos) have regenerative properties that can repair cartilage damage, lower blood sugar levels, and improve pancreatic β cell function, showing great potential in tissue repair. This review primarily explores the application of MSC-Exos in the treatment of OA and T2DM, the potential mechanisms of MSC-Exos, and the therapeutic strategies of engineered exosomes. Although MSC-Exo therapy shows promising therapeutic potential, further research is needed to validate its safety and feasibility.